Welcome - Senathirajah, Pathman; VStudios ([S.l.] : VStudios, 2008)
This video gives an overview of Questnet products - health and wellness, personal care, telecommunications, luxury products under the brands BH Mayer and Qatana, and vacation packages under Quest Vacation International
Title from title screen
DVD format
Keywords: Multilevel marketing; Direct marketing